Comunicação organizacional e as marcas discursivas das marcas na contemporaneidade - Jungkenn, Glória Rückert (2023)
In the present Dissertation, as an open-air work, we seek to approximate organizational communication and brands, from the discourses manifested in the contemporary context. For the development of the research, we propose the following objectives: to discuss the possible interfaces between organizational communication and brands; reflect on possible understandings of the brand universe from the perspective of organizational communication; and; to analyze the discursive brands triggered by the NIVEA and Natura brands from their contemporary discourses. The investigation resorts to a bibliographical and documental review (GIL, 2008; STUMPF, 2006) with the purpose of outlining our theoretical-reflective tracks that accompanied us during the course of the study. In order to understand the interlocutions between organizational communication and brands, we resorted to the State of the Art based on the CAPES Theses and Dissertations catalog and on the Congress' papers. Proposals for brand (re)readings are anchored in complexity paradigm (MORIN, 2019, 2015a, 2015b) and in systemic paradigm (CAPRA, 2006, 2002; MATURANA; VARELA, 2001), because of the quest to get out of linear views. To analyze the contemporary discourses of brands, we selected Discourse Analysis (DA) as a methodological procedure according perspectives of Orlandi (2020, 2017) and Pêcheux (2015, 2014), from which we delimited the analytical device, the corpus and the dimensions of analysis. For brand selection, we opted for the beauty sector and selected the materials available from NIVEA and Natura in the digital medium based on concepts of well-being, care and affection. These choices allowed us to analyze the discursive brands of the brands and their intersections. We recognize that these brands have expanded to different contexts due to their characteristics of flexibility, hybridity, adaptation and formation of bonds as social actors, discourses and narratives before the public, building symbiotic relationships with organizations and with communication.